Gymnastics - Schwartz, Heather E.; Gale (Firm) (Detroit, Mich. : Lucent Books, 2011)
Explores the scientific principles behind some of the most popular team and individual sports. Covers origins, history and changes, the biomechanics and physiology of playing, related health and medical concerns, and the causes and treatment of sports-related injuries. This volume covers gymnastics.
ch 1. An ancient sport -- ch 2. Training and conditioning -- ch 3. Somersaults, headstands, and other beginner moves -- ch 4. Flying high -- ch 5. Injuries and treatments -- ch 6. The psychology of gymnastics.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Gymnastics